An Infant Case with Hair-Thread Tourniquet Syndrome - Fatih İşleyen; Mehmet Tekin (Galenos Yayinevi, 2019)
Strangulation of the limbs by wrapping them with hair or thread leads to a syndrome called hair-thread tourniquet syndrome. If early diagnosis and correct treatment is not performed, it may result in loss of the affected tissues. The time between the development of the event and the removal of the hair-thread is important. In this paper, a 2.5-month-old girl with swelling of the 3rd and 4th toes of the left foot due to hair entanglement is presented.